Nurses’ perceived demands and burnout level in the critical care units during the COVID-19 pandemic crisis - Samah Abdulwahed Ali (Nursing Practice Today)
Background & Aim: The coronavirus disease (COVID-19) pandemic challenged the physical and psychological well-being of critical care nurses because of the increasing number of infected patients, demands of care, and shortage of healthcare front-liners, particularly nurses. This study determined nurses’ perceived demands and the significant predictors of their burnout level in critical care units of tertiary hospitals in Saudi Arabia during the COVID-19 pandemic crisis. Methods & Materials: This study used a cross-sectional research design. It was conducted from November to December 2021. Two hundred seventy nurses working in critical care units of tertiary hospitals in Saudi Arabia were surveyed using adopted questionnaires. Results: The findings of this study revealed that the nurses’ demands concerning safety, communication, and relationships between team members, and psycho-socio-emotional aspects were moderate, whereas their demands concerning organization and decision-making were slight. Furthermore, nurses’ levels of emotional exhaustion and depersonalization/ loss of empathy were high, and personal accomplishment was low, which indicates a high level of occupational burnout. Interestingly, the correlations between the dimensions of burnout and perceived demands were highly significant (p<0.001). Conclusion: The safety demands of critical care nurses significantly predicted emotional exhaustion due to an increased workload during COVID-19. The demands were significant predictors of depersonalization and personal accomplishment due to their perception that staff shortage, imbalanced workload, increasing care demand, and fatigue might have compromised the quality of patient care. Nurses experienced increased emotional distress and frustration in conveying their feelings of exhaustion, which led to high burnout levels during COVID-19.